Human multipotent adult progenitor cells effectively reduce graft‐vs‐host disease while preserving graft‐vs‐leukemia activity. (28th July 2021) - Metheny, Leland; Eid, Saada; Wuttisarnwattana, Patiwet; Auletta, Jeffery J.; Liu, Chen; Van Dervort, Alana; Paez, Conner; Lee, ZhengHong; Wilson, David; Lazarus, Hillard M.; Deans, Robert; Vant Hof, Wouter; et al.
Abstract: Graft‐vs‐host disease (GvHD) limits successful outcomes following allogeneic blood and marrow transplantation (allo‐BMT). We examined whether the administration of human, bone marrow‐derived, multipotent adult progenitor cells (MAPCs™) could regulate experimental GvHD. The immunoregulatory capacity of MAPC cells was evaluated in vivo using established murine GvHD models. Injection of MAPC cells on day +1 (D1) and +4 (D4) significantly reduced T‐cell expansion and the numbers of donor‐derived, Tumor Necrosis Factor Alpha (TNFα) and Interferon Gamma (IFNγ)‐producing, CD4+ and CD8+ cells by D10 compared with untreated controls. These findings were associated with reductions in serum levels of TNFα and IFNγ, intestinal and hepatic inflammation and systemic GvHD as measured by survival and clinical score. Biodistribution studies showed that MAPC cells tracked from the lung and to the liver, spleen, and mesenteric nodes within 24 hours after injection. MAPC cells inhibited mouse T‐cell proliferation in vitro and this effect was associated with reduced T‐cell activation and inflammatory cytokine secretion and robust increases in the concentrations of Prostaglandin E2 (PGE2) and Transforming Growth Factor Beta (TGFβ). Indomethacin and E‐prostanoid 2 (EP2) receptor antagonism both reversed while EP2 agonism restored MAPC cell‐mediated in vitro T‐cell suppression, confirming the role for PGE2. Furthermore, cyclo‐oxygenase inhibition following allo‐BMT abrogated the protective effects of MAPC cells. Importantly, MAPC cells had no effect on the generation cytotoxic T lymphocyte activity in vitro, and the administration of MAPC cells in the setting of leukemic challenge resulted in superior leukemia‐free survival. Collectively, these data provide valuable information regarding the biodistribution and regulatory capacity of MAPC cells, which may inform future clinical trial design. Abstract : Bio‐redistribution of multipotent adult progenitor cells from the lung and to the liver and spleen of allogeneic blood and marrow transplantation recipient mice as captured by 3D, computer‐generated imagery.